2020
DOI: 10.1166/jnn.2020.17340
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Scanning on Nano Crystalline β-Ti Alloys Fabricated by Selective Laser Melting and Their Applications in Biomedical Science

Abstract: The present study focuses on the microstructural and bioactive properties evolution in selective laser melting (SLM) β titanium alloys. We have applied cross-scan strategy for improving mechanical properties and lower elastic modulus of SLMed Ti–20Mg–5Ta alloys which has been shown to be altering the microstructure and refining the grain size. The cross-scan strategy can refine the microstructure and induce various deformation textures in contrast to the conventional scan st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, excessive Trp may produce a toxic waste in the brain, causing delusions and hallucinations [2]. In addition, it is thought to be a possible cause of schizophrenia in humans who cannot metabolize it properly [3][4][5]. Because of this clinical background, a convenient quantitative method for Trp is expected to bring many medical benefits.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive Trp may produce a toxic waste in the brain, causing delusions and hallucinations [2]. In addition, it is thought to be a possible cause of schizophrenia in humans who cannot metabolize it properly [3][4][5]. Because of this clinical background, a convenient quantitative method for Trp is expected to bring many medical benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant WO 3 microbowl array film showed superior electrochromic property with coloration efficiency of 68 cm 2 C −1 , response times of 3.6 s (coloration) and 1.0 s (bleaching) in comparison with the dense film prepared without a PS template. Compared with the template method, simultaneous electrodeposition of WO 3 and other nanomaterials for fabrication of composite WO 3 film is more convenient and efficient in creation of a porous structure in WO 3 film [33][34][35]. Song et al [36] reported the fabrication of porous WO 3 film by electrochemically polymerizing 3-chlorothiophene on the surface of WO 3 film in the ionic liquid 1-butyl-3-metyllimidazolium hexafluorophosphate.…”
Section: Introductionmentioning
confidence: 99%